Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Weight Loss and Alzheimer's Disease in Down Syndrome. - Fleming, Victoria; Helsel, Brian C; Ptomey, Lauren T; Rosas, H Diana; Handen, Benjamin; Laymon, Charles; Christian, Bradley T; Head, Elizabeth; Mapstone, Mark; Lai, Florence; Krinsky-McHale, Sharon; Zaman, Shahid; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Virtually all adults with Down syndrome (DS) develop Alzheimer's disease (AD) pathology, but research gaps remain in understanding early signs of AD in DS. OBJECTIVE: The goal of the present study was to determine if unintentional weight loss is part of AD in DS. The specific aims were to: 1) examine relation between chronological age, weight, AD pathology, and AD-related cognitive decline were assessed in a large cohort of adults with DS, and 2) determine if baseline PET amyloid-β (Aβ) and tau PET status (-versus+) and/or decline in memory and mental status were associated with weight loss prior to AD progression. METHODS: Analyses included 261 adults with DS. PET data were acquired using [11C] PiB for Aβ and [18F] AV-1451 for tau. Body mass index (BMI) was calculated from weight and height. Direct measures assessed dementia and memory. Clinical AD status was determined using a case consensus process. Percent weight decline across 16-20 months was assessed in a subset of participants (n = 77). RESULTS: Polynomial regressions indicated an 0.23 kg/m2 decrease in BMI per year beginning at age 36.5 years, which occurs alongside the period during which Aβ and tau increase and memory and mental status decline. At a within-person level, elevated Aβ, decline in memory and mental status were associated with higher percent weight loss across 16-20 months. CONCLUSION: Unintentional weight loss occurs alongside Aβ deposition and prior to onset of AD dementia, and thus may be a useful sign of AD in DS.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Selective Impairment of Long-Range Default Mode Network Functional Connectivity as a Biomarker for Preclinical Alzheimer's Disease in People with Down Syndrome. - DiProspero, Natalie D; Keator, David B; Phelan, Michael; van Erp, Theo G M; Doran, Eric; Powell, David K; Van Pelt, Kathryn L; Schmitt, Frederick A; Head, Elizabeth; Lott, Ira T; Yassa, Michael A (J Alzheimers Dis, 2021)
BACKGROUND: Down syndrome (DS) is associated with increased risk for Alzheimer's disease (AD). In neurotypical individuals, clinical AD is preceded by reduced resting state functional connectivity in the default mode network (DMN), but it is unknown whether changes in DMN connectivity predict clinical onset of AD in DS. OBJECTIVE: Does lower DMN functional connectivity predict clinical onset of AD and cognitive decline in people with DS? METHODS: Resting state functional MRI (rsfMRI), longitudinal neuropsychological, and clinical assessment data were collected on 15 nondemented people with DS (mean age = 51.66 years, SD = 5.34 years, range = 42-59 years) over four years, during which 4 transitioned to dementia. Amyloid-β (Aβ) PET data were acquired on 13 of the 15 participants. Resting state fMRI, neuropsychological, and clinical assessment data were also acquired on an independent, slightly younger unimpaired sample of 14 nondemented people with DS (mean age = 44.63 years, SD = 7.99 years, range = 38-61 years). RESULTS: Lower functional connectivity between long-range but not short-range DMN regions predicts AD diagnosis and cognitive decline in people with DS. Aβ accumulation in the inferior parietal cortex is associated with lower regional DMN functional connectivity. CONCLUSION: Reduction of long-range DMN connectivity is a potential biomarker for AD in people with DS that precedes and predicts clinical conversion.

Down Syndrome, Partial Trisomy 21, and Absence of Alzheimer's Disease: The Role of APP. - Doran, Eric; Keator, David; Head, Elizabeth; Phelan, Michael J; Kim, Ron; Totoiu, Minodora; Barrio, Jorge R; Small, Gary W; Potkin, Steven G; Lott, Ira T (J Alzheimers Dis, 2017)
Overexpression of the amyloid precursor protein (APP) gene on chromosome 21 in Down syndrome (DS) has been linked to increased brain amyloid levels and early-onset Alzheimer's disease (AD). An elderly man with phenotypic DS and partial trisomy of chromosome 21 (PT21) lacked triplication of APP affording an opportunity to study the role of this gene in the pathogenesis of dementia. Multidisciplinary studies between ages 66-72 years comprised neuropsychological testing, independent neurological exams, amyloid PET imaging with 11C-Pittsburgh compound-B (PiB), plasma amyloid-β (Aβ) measurements, and a brain autopsy examination. The clinical phenotype was typical for DS and his intellectual disability was mild in severity. His serial neuropsychological test scores showed less than a 3% decline as compared to high functioning individuals with DS who developed dementia wherein the scores declined 17-28% per year. No dementia was detected on neurological examinations. On both PiB-PET scans, the patient with PT21 had lower PiB standard uptake values than controls with typical DS or sporadic AD. Plasma Aβ42 was lower than values for demented or non-demented adults with DS. Neuropathological findings showed only a single neuritic plaque and neurofibrillary degeneration consistent with normal aging but not AD. Taken together the findings in this rare patient with PT21 confirm the obligatory role of APP in the clinical, biochemical, and neuropathological findings of AD in DS.

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

A Novel Liposomal Nanoparticle for the Imaging of Amyloid Plaque by Magnetic Resonance Imaging. - Tanifum, Eric A; Ghaghada, Ketan; Vollert, Craig; Head, Elizabeth; Eriksen, Jason L; Annapragada, Ananth (J Alzheimers Dis, 2016)
Amyloid binding molecules with greater hydrophilicity than existing ligands were synthesized. The lead candidate ET6-21 bound amyloid fibrils, and amyloid deposits in dog brain and human brain tissue ex vivo. The ligand was used to prepare novel amyloid-targeted liposomal nanoparticles. The preparation was tested in the Tg2576 and TetO/APP mouse models of amyloid deposition. Gd chelates and Indocyanine green were included in the particles for visualization by MRI and near-infrared microscopy. Upon intravenous injection, the particles successfully traversed the blood-brain barrier in these mice, and bound to the plaques. Magnetic resonance imaging (T1-MRI) conducted 4 days after injection demonstrated elevated signal in the brains of mice with amyloid plaques present. No signal was observed in amyloid-negative mice, or in amyloid-positive mice injected with an untargeted version of the same agent. The MRI results were confirmed by immunohistochemical and fluorescent microscopic examination of mouse brain sections, showing colocalization of the fluorescent tags and amyloid deposits.